2021
DOI: 10.1111/iju.14671
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of narrow band imaging for non‐muscle‐invasive bladder cancer

Abstract: To assess the effect of narrow band imaging-guided transurethral resection of bladder tumor compared with white light on recurrence rates in non-muscle-invasive bladder cancer. A systematic review of the literature from inception to November 2020 using Medline, EMBASE and CENTRAL was undertaken. Randomized controlled trials comparing transurethral resection of bladder tumor undertaken with narrow band imaging with those undertaken with white light that reported recurrence rates of at least 12 months were inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…36,[41][42][43] In a combined analysis of six randomized control trials (RCT's), one systematic review found improved recurrence for NBI plus white light versus white light alone in patients with suspected or confirmed NMIBC (HR: 0.63; 95% CI: 0.45 to 0.89; I 2 [ 53%; 6 RCTs, 1244 patients). 42 The other three systematic reviews found no difference in recurrence with white light versus white light D NBI cystoscopy 36,37,44 The Panel acknowledges that NBI technology is readily available to many clinicians. While not proven to decrease recurrence, there is no evidence of additional risk incurred by patients with its use.…”
Section: Guideline Statements Variant Histologiesmentioning
confidence: 99%
“…36,[41][42][43] In a combined analysis of six randomized control trials (RCT's), one systematic review found improved recurrence for NBI plus white light versus white light alone in patients with suspected or confirmed NMIBC (HR: 0.63; 95% CI: 0.45 to 0.89; I 2 [ 53%; 6 RCTs, 1244 patients). 42 The other three systematic reviews found no difference in recurrence with white light versus white light D NBI cystoscopy 36,37,44 The Panel acknowledges that NBI technology is readily available to many clinicians. While not proven to decrease recurrence, there is no evidence of additional risk incurred by patients with its use.…”
Section: Guideline Statements Variant Histologiesmentioning
confidence: 99%
“…We thank Dr G omez-Ospina and Dr Garc ıa-Perdomo for the interesting points raised in their letter to the editor regarding our recent systematic review. 1,2 The main point highlighted was the potential for the methodological selections made within our review to influence decision-making. They cite prior systematic reviews that report more definitive findings than our own, but use a wider range of evidence, including observational studies.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…1 NMIBC accounts for 75% of newly diagnosed BCs. 2,3 TURBT and subsequent intravesical instillation of BCG remain the standard of care for preventing recurrence and progression to MIBC in patients with high-risk NMIBC. [4][5][6] However, a significant number of patients experiences recurrence and progression despite adjuvant BCG therapy.…”
Section: Introductionmentioning
confidence: 99%
“…BC is the ninth most common cancer in the world 1 . NMIBC accounts for 75% of newly diagnosed BCs 2,3 …”
Section: Introductionmentioning
confidence: 99%